2012
DOI: 10.1111/j.1469-7998.2012.00947.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative genetics of basal metabolic rate and body mass in free‐living pied flycatchers

Abstract: Despite basal metabolic rate (BMR) being one of the most commonly measured physiological traits and an important indicator of competitive ability, very little is known about its genetic basis and relation to other physiological traits. Here, we present the first attempt to estimate the multivariate basis of BMR using a natural population of pied flycatcher Ficedula hypoleuca breeding in the Tomsk Region, Western Siberia. We show relatively high and significant heritability of whole‐organism BMR, mass‐specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
24
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 40 publications
7
24
4
Order By: Relevance
“…The heritability of BMR found in our study (h 2 ¼ 0.45) was higher than that reported in an earlier study in the same species (h 2 ¼ 0.25; Rønning et al, 2007) and closer to the heritabilities previously reported for free-living passerines (blue tits, Cyanistes caeruleus, h 2 ¼ 0.59 (Nilsson et al, 2009), and pied-flycatchers, Ficedula hypoleuca, h 2 ¼ 0.43, (Bushuev et al, 2012)). This suggests that between-study differences in the quantitative genetics of BMR are not merely the result of a dichotomy between lab versus field populations, as has previously been suggested (Bushuev et al, 2012).…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…The heritability of BMR found in our study (h 2 ¼ 0.45) was higher than that reported in an earlier study in the same species (h 2 ¼ 0.25; Rønning et al, 2007) and closer to the heritabilities previously reported for free-living passerines (blue tits, Cyanistes caeruleus, h 2 ¼ 0.59 (Nilsson et al, 2009), and pied-flycatchers, Ficedula hypoleuca, h 2 ¼ 0.43, (Bushuev et al, 2012)). This suggests that between-study differences in the quantitative genetics of BMR are not merely the result of a dichotomy between lab versus field populations, as has previously been suggested (Bushuev et al, 2012).…”
Section: Discussioncontrasting
confidence: 56%
“…Quantitative genetic analyses of BMR can inform us about the evolvability of the trait by providing estimates of both narrow-sense heritability (h 2 ) and of genetic correlations with other behavioural or morphological traits that may constrain the ability of BMR to respond to selection. Despite being one of the most widely measured physiological traits, there are relatively few studies to date that have explicitly investigated the heritability of BMR, and even fewer that have attempted to estimate genetic correlations between BMR and other traits (but see Nespolo et al, 2005;Rønning et al, 2007;Gebczynski and Konarzewski, 2009;Nilsson et al, 2009;Tieleman et al, 2009;Wone et al, 2009;Careau et al, 2011;Bushuev et al, 2012). Furthermore, these studies have produced conflicting results.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…[35][36][37]), mammals (e.g. [51,52]) and chickens [53], but the static scaling exponent of metabolic rate is almost isometric in adult pied flycatchers Ficedula hypoleuca [54], and metabolic rate and body mass are independent in some (e.g. [55]), but not all (e.g.…”
Section: Discussion (A) Allometric Scaling Of Metabolism and The Benementioning
confidence: 99%